Solar Biota. Co-Living with Solar Ecologies - Suzanna Törnroth (Pad)
Solar energy (technology) has often become synonymous with the solar photovoltaic (PV) panel within global decarbonisation efforts, leading to a disproportionate focus on the anthropogenic and techno-economic benefits of solar energy use within modern consumption patterns. However, solar PV could otherwise be understood as a technoecological phenomenon – broadly conceived as indeterminate associations of living and non-living ways of being. Through the lens of artistic research combined with the new materialist tradition, this article elaborates on a multispecies ethnographic study which was conducted over a five-month long period. The study is based on a multispecies (co)living with the SunSpider: a prototyped, small-scale, solar PV thing, installed in the outdoor context of an intimate domestic environment. The results of the study offer poetic insight into the entangled ecological, weather and climatic narratives that ensued in place, explained through a medium of multispecies storytelling. Importantly, the discussion relates to the notion of care, and how the SunSpider’s form and function fostered an emotional attunement between the human and non-human study participants. The central question to this study is thus – How might a relational adoption of solar PVs increase multispecies flourishing? The article culminates in the explanation of ‘solar ecologies’, which offers a point of departure in exploring relational complexities in co(living) with solar PV – and solar energy symbolically, at large.